Pengaruh Persahabatan Terhadap Kesejahteraan Hidup Manusia - Kurniawan Dwi Madyo Utomo (Seri Filsafat Teologi, 2020)
Friendships are fundamental to human social life. Therefore, people try every great effort to build and maintain these friendships. The aim of this paper is to discuss the effect of friendship on the well-being of individuals at every stage of human development. The method used to achieve this goal is to explore the results of studies related to friendship and its effect on human well-being. The results of these studies indicate that friendship can be related to well-being. Healthy friendships help people to adjust and give them happiness. Happy people also tend to try to build and maintain friendships. Contrarily, unhealty friendships lead to loneliness and depression. Friendships which has been built since childhood also affects the well-being of an individual’s life at the later stages of human development.